Diagnostic value of pre-operative upper GI endoscopy in gall bladder stone patients undergoing elective laparoscopic cholecystectomy - Srikantaiah, Hiremath Chandrasekharaiah; Manjappa, Vinay Bhadrapura (International Surgery Journal, 2019)
Background: Cholecystectomy does not offer all symptomatic relief in most of the patients because of an overlap in the symptomology of biliary and gasroduodenal pathologies. Thus, we aimed at evaluating the efficacy of upper gastrointestinal endoscopy (UGE) in all patients with upper abdominal pain irrespective of ultrasound findings or symptoms. Methods: This prospective study was carried out from November 2015 – August 2017. Patients above 18 years, with ultrasonographically proven diagnosis of cholelithiasis, undergoing laparoscopic cholecystectomy by a single surgeon were studied. UGE was referred to all patients before surgery. Descriptive statistics was used to analyze pathological UGE findings and corresponding 95% confidence levels (CI) was calculated. Results: A total of 117 patients were included in this study with a mean age of 43.6±13.8 years. Majority of the patients were women (59.8%) and most of them presented atypical biliary colic symptoms (n=64, 54.7%). UGE of patients with biliary colic symptoms showed that 65.8% of patients had normal endoscopy findings when compared to 34.2% of patients had positive endoscopy findings. Significantly higher proportion patients with positive UGE findings presented atypical biliary (70%, n=28) when compared to typical biliary colic patients with positive findings (30%, n=12; p<0.05). Among patients being positive for UGE detected lesions, gastritis (~18%), followed by duodenal ulcer (10%) and reflux esophagitis (5%) were the common upper GI problems observed. Conclusions: Pre-elective and routine use of UGE before laparoscopic cholecystectomy helps in reducing persistence of symptoms and in treatment management.